A APS uma referência para São Tomé e Príncipe - Lavres, Elvídio António Fernandes da Costa (2018)
The reason for the present investigation is related to the potential that IT Systems and the concepts of Single Window and Port Community Systems can endow to the port and port business, and in particular the new Port Single Invoice project. The Port Single Invoice involves the shipping agents as representatives of the vessels/shipowners/owners, and the public entities that provide services to the ship, and started operating in the Portuguese ports on 01-01-2017. The research was headed by APS-Administration of the Ports of Sines and Algarve, S.A., specifically in the port of Sines, being the report more focused on the investigation process than on the results. The research is empirical and qualitative, allowing an exploratory only, with the purpose of leading the way to the construction of future hypotheses, comprising the current internship report a synthesis of the international, European and Portuguese concerns on dematerialization and simplification of the processes related to maritime transport. The qualitative case study method was used, as well as data collection, document analysis, direct and participant observation, a questionnaire survey of shipping agents authorized to perform their activity in the port of Sines, using the nonprobabilistic sample as the sampling technique. For the construction of the survey, a general hypothesis and an operational hypothesis based on the determinants of the Resolution of the Council of Ministers nº 12/2016, of 16-3, was applied, in order to ascertain the perception of shipping agents about the Port Single Invoice. From the questionnaire applied, it was concluded that the sample used was significant, since the coefficient of variation returned a range between 10.52% and 36.39%.